Polysulfone (PSF)/Silicoaluminophosphate (SAPO-34) Membrane Incorporated With 1-Ethyl-3 Methylimidazoliumbis (TRIFLUOROMETHYSULFONYL) Imide [EMIM][TF2N] For Carbon Dioxide Separation - Ng, Won Huei (Universiti Sains Malaysia, 2018)
Carbon dioxide (CO2) is the main contributor to greenhouse effect since industrial revolution. Ionic liquids (ILs) have been extensively studied in the recent years to improve the performance of CO2 separation due to the high CO2 solubility and selectivity. In this study, imidazolium-based ionic liquid was used to improve and functionalise the interface between polysulfone (PSf) and SAPO-34 zeolite in the asymmetric mixed matrix membrane (MMM) which was prepared by phase inversion method for minimum mass transfer resistance. PSf/SAPO-34 MMMs were post-modified by immersing the membranes into IL solution (1-Ethyl-3 Methylimidazoliumbis (Trifluoromethysulfonyl) Imide). The main objective of this work is to study the effects of IL concentration on the membrane morphology and separation performance in CO2. The morphology of the IL modification by using scanning electron microscopy (SEM) proved the well dispersion of SAPO-34 subjected to improve polymer/filler interface. The fourier transform infrared spectra (FTIR) were also confirmed that IL was successfully incorporated into MMM andrecorded to check the existence bond in the membrane sample. The post-impregnation of the membrane with IL improved the interface contact between the polymer and zeolite. The interface sealing using 0.2M IL enhanced the CO2 permeance, both of the CO2/N2 and CO2/CH4 selectivity of IL-modified MMM, about 319.73 %, 601.69 % and 605.84 % higher than the CO2/N2 and CO2/CH4 selectivity of unmodified MMMs.